KONTRIBUSI SEKTOR PERTANIAN TERHADAP PEREKONOMIAN KABUPATEN BOLAANG MONGONDOW UTARA - Findriani ., Lumikis; Celsius ., Talumingan; Sherly G. Jocom (AGRI-SOSIOEKONOMI, 2021)
This research is conducted  in order to analyze the contribution of the agricultural sector toward the economy of North Bolaang Mongondow Regency in the period of 8 years, 2010 to 2017, and also in order to identify the agricultural sector and sub-sector is the base sector in North Bolaang Mongondow Regency. This research was conducted for three months started from December 2019 to January 2020 at the Central Statistics Agency of North Bolaang Mongondow Regency and the Central Statistics Agency of North Sulawesi Province. The data used are secondary data. Where secondary data were obtained from the Central Statistics Agency of North Bolaang Mongondow Regency and the Central Statistics Agency of North Sulawesi Province. The data analysis used is the contribution formula, Location Quotient analysis and Dynamic Location Quotient method. The results of this study indicates that the agricultural, forestry and fisheries sectors are the largest contributors or major contributors to the economy of North Bolaang Mongondow Regency from 2010 to 2017. Based on the result analysisof the Location Quotient it can be seen that the agricultural, forestry and fisheries sectors are the basic sectors in North Bolaang Mongondow Regency. It means, this sector is able to fulfill the necessity for their own  region and it  is  also possible to do  exporting  to  outside  of  region. Furthermore, the sub-sector which is the base sector in North Bolaang Mongondow Regency is the forestry sub-sector. The crop subsector and the annual horticultural  subsector contained in the agriculture, livestock and agricultural services sub-sector are also the base sectors in North Bolaang Mongondow  Regency.